2024
DOI: 10.1371/journal.pone.0298720
|View full text |Cite
|
Sign up to set email alerts
|

Understanding paleo-earthquakes in the Kuril Trench based on Late-Holocene tsunami deposits in the distal region from wave sources, northern Hidaka, Hokkaido, Japan

Ryo Nakanishi,
Juichiro Ashi,
Satoshi Okamura
et al.

Abstract: Geological evidence, such as tsunami deposits, is crucial for studying the largest rupture zone of the Kuril Trench in Hokkaido, Japan, due to its poor historical record. Although 17th-century tsunami deposits are widely distributed across Hokkaido, the presence of multiple wave sources during that period, including the collapse of Mt. Komagatake, complicates the correlation with their wave sources. Understanding the regional distribution of these tsunami deposits can provide valuable data to estimate the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…2 and 3). The KS1 layer shows the inverse to normal grading structure and is induced by the inundation over the beach ridge because it contains coarse-grained sand that is constated of the beach ridge and beach sand (Nakanishi et al, 2024). The Komagatake model also reproduces the features of the KS1 layer in the grading structure by bedload and suspension and poor sorting (Fig.…”
Section: Parameter Settingmentioning
confidence: 84%
See 3 more Smart Citations
“…2 and 3). The KS1 layer shows the inverse to normal grading structure and is induced by the inundation over the beach ridge because it contains coarse-grained sand that is constated of the beach ridge and beach sand (Nakanishi et al, 2024). The Komagatake model also reproduces the features of the KS1 layer in the grading structure by bedload and suspension and poor sorting (Fig.…”
Section: Parameter Settingmentioning
confidence: 84%
“…In Kabari, the 17th-century tsunami deposits were reported by Takashimizu et al (2017) and reexamined by Nakanishi et al (2024). They found a total of ve sand layers in the peat layer and reported that the two sand layers were different event layers that occurred in the 15th-17th century.…”
Section: Tsunami Deposit Datamentioning
confidence: 99%
See 2 more Smart Citations